Enhanced selectivity in detecting matrix metalloproteinase-2 via sequential affinity capture, cascade reaction, and electrochemical measurement - Park, Seonhwa; Gwon, Minji; Lee, Hyeryeong; Kim, Seonghye; Kim, Suhkmann; Joo, Jung Min; Yoo, Tae Hyeon; Yang, Haesik (Sensors and Actuators B: Chemical, 2025)
Selective detection of proteases in complex biological matrices remains a significant challenge due to interference from multiple proteases and inhibitors. This study introduces a novel method for the selective and sensitive detection of matrix metalloproteinase-2 (MMP-2) employing a sequence of affinity capture, cascade reaction, and electrochemical measurement. The method begins with the affinity capture of MMP-2 on an electrode, followed by a washing step to mitigate interference from other proteases and inhibitors present in human serum. This is followed by a cascade reaction, where proteolytic cleavage of auto-inhibited β-lactamase by MMP-2 and subsequent ring-opening hydrolysis of electro-inactive nitrocefin by the activated β-lactamase rapidly produce electro-active open-nitrocefin. Electrochemical measurements of this open-nitrocefin near the electrode surface generate a high signal. This method achieved a detection limit of 20 ng/mL for MMP-2 in human serum and demonstrated high selectivity against a range of proteases. The study presents a new strategy for the selective and sensitive detection of proteases in complex biological samples, potentially enhancing diagnostic approaches for protease-related diseases.
Keywords: Cascade reactions; ELectrochemical detection; Electrochemical measurements; Engineered auto-inhibited β-lactamase; Matrix metalloproteinase-2; Nitrocefin; Protease; Selective detection; Sensitive detection; β-Lactamase; Cascade reaction; Electrochemical detection; Engineered auto-inhibited β-lactamase; Matrix metalloproteinase-2; Protease